The first combined search for neutrino point-sources in the southern hemisphere with the ANTARES and IceCube Neutrino Telescopes - Adrian Martinez, S.; Albert, A.; André, M.; Anton, G.; Ardid, M.; Golup, Geraldina Tamara; Vraeghe, M.; Walck, C.; Wallace, A.; Wallraff, M.; Wandkowsky, N.; Weaver, Ch.; et al. (IOP Publishing, 2016)
Fil: Adrian Martinez, S.. Universidad Politécnica de Valencia; España